Effect of Nutmeg on Collagen Remodeling and Epithelialization Using Picrosirius Red and Gold-Orange Staining - Fitri, Maisyithoh Rahma; Husna, Fauzul; Suryadi, Taufik; Sary, Nirwana Lazuardi; Fitria, Fitria; Sari, Widya; Maisun, Maisun (Indonesian Journal of Pharmaceutical Science and Technology, 2026)
Burn injuries, especially second-degree burns, remain a global health concern. Their complex healing mechanisms and socioeconomic burden make them challenging to treat.  This study evaluates the effects of 3% nutmeg (Myristicafragrans) cream on collagen remodeling and epithelial regeneration in grade II burns, using advanced histological techniques.  A post-test-only experimental design was used. Five groups were included: normal control, untreated burn, burn treated with nutmeg cream, burn treated with silver sulfadiazine (SSD), and burn treated with both nutmeg cream and SSD. Collagen subtype distribution was examined using Picrosirius Red–Fast Green staining under polarized light. Epithelialization was assessed using Gold-Orange staining. Results showed that nutmeg cream significantly enhanced the transition from collagen type III to type I. It improved epithelial thickness and promoted keratohyalin granule formation compared to untreated burns. The combination therapy improved some histological features but did not consistently outperform single therapy by day 18. These findings indicate that nutmeg cream supports extracellular matrix remodeling and epithelial maturation. This validates its traditional use and suggests its potential as an accessible adjunctive therapy.  Overall, this study underscores the value of integrating plant-based bioactives with standard treatments to improve burn wound healing.